Right Atrial Collision Time (RACT): a novel marker of propensity for typical atrial flutter. (25th November 2020) - Crinion, D; Al-Turki, M; Al Hammad, N; Neira, V; De Leon, A; Abdollah, H; Chacko, S; Enriquez, A; Simpson, C; Baranchuk, A; Johri, A; Redfearn, D
Abstract: Background: The risk of typical atrial flutter (AFL) is increased by factors that increase right atrial (RA) size or cause scarring to reduce conduction velocity. These characteristics ensure the macro re-entrant wave front does not meet its refractory tail. The time taken to traverse the circuit would take account of both of these characteristics (being equal to distance divided by velocity), and may provide a superior marker of propensity to develop AFL. Purpose: To investigate right atrial collision time (RACT) as a marker of typical AFL. Methods: This single centre, prospective study recruited consecutive typical AFL ablation cases that were in sinus rhythm. Controls were consecutive cases other than atrial fibrillation and >50 years of age. Exclusion criteria for both groups were a prior ablation in the RA and class I and III antiarrhythmics. While pacing the coronary sinus ostium at 600 ms, a local activation time map was created to locate the latest collision point on the anterolateral wall, excluding the RA appendage (Figure 1). This RACT approximates half a revolution. Results: The AFL group's (n=34) mean RACT was 132.5±15.06 vs 98.7±12.23ms in the controls (n=40) (p<0.01). No significant difference was observed for age (mean 65.6 vs 62.6 (p=0.18)), male (68.8% vs 60% (p=0.59)), body surface area (mean 2.1 vs 2.03 m 2 (p=0.24)). The RACT also proved to be a superior marker than the echocardiographic measurement of right atrial area in an apical four chamber view (mean 17.8 vs 16.3 cm 2 (p=0.21).A ROC curve indicated an AUC of 0.97 (95% CI: 0.93–1.0, p<0.01). A RACT cut-off of 120 ms had a specificity of 99% and a sensitivity of 75%. Conclusion: RACT is a novel and promising marker of propensity for typical AFL. The ability to predict AFL would be of significant clinical value given the risk of stroke and frequent need for ablation. Funding Acknowledgement: Type of funding source: None